TAIGA - an advanced hybrid detector complex for astroparticle physics and high energy gamma-ray astronomy in the Tunka valley - Budnev, N; Astapov, I; Bezyazeekov, P; Bonvech, E; Boreyko, V; Borodin, A; Bruckner, M; Bulan, A; Chernov, D; Chernykh, D; Chiavassa, A; Dyachok, A; et al. (Journal of Instrumentation, 2020)
The TAIGA observatory addresses ground-based gamma-ray astronomy at energies from a few TeV to several PeV, cosmic ray physics from 100 TeV to several EeV as well as for search for axion-like particles, Lorentz violations and another evidence of New Physics. In 2020 year a one square kilometer TAIGA setup should be put in operation.